2010
DOI: 10.1111/j.1743-6109.2009.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Quality of Life in Women with Urinary Incontinence Treated by a Complete Pelvic Floor Rehabilitation Program (Biofeedback, Functional Electrical Stimulation, Pelvic Floor Muscles Exercises, and Vaginal Cones)

Abstract: Introduction Urinary incontinence (UI) is a debilitating condition that can cause discomfort, embarrassment, loss of confidence; it can lead to withdrawal from social life, and adversely affects physical and mental health, sexual function and quality of life (QoL) in women. Aim The aim is to determine the impact of combined pelvic floor rehabilitation (PFR) on UI, female sexual dysfunction, and QoL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 31 publications
4
30
1
6
Order By: Relevance
“…Our results are in agreement with the study of Rivalta et al indicating that 82% of patients treated with hemodialysis are suffering from sexual dysfunction (14).…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in agreement with the study of Rivalta et al indicating that 82% of patients treated with hemodialysis are suffering from sexual dysfunction (14).…”
Section: Discussionsupporting
confidence: 83%
“…Most of them showed that UI adversely affects women's sexual life, mental health, and social life [21][22][23]. We observed decreased prevalence of UI in sexually active respondents.…”
Section: Discussionmentioning
confidence: 54%
“…Sixty four patients (aged [16][17][18][19][20][21][22][23][24] Twenty eight respondents (44%) reported being urine incontinent. There were no differences in age, BMI, FEV1, CFRD and PEG between continent and incontinent respondents.…”
Section: Resultsmentioning
confidence: 99%
“…A literatura internacional [5][6][7] e nacional 8,9 apontam maior repercussão negativa sobre a qualidade de vida (QV) nos casos de urge-incontinência do que nos outros tipos de IU.…”
Section: Introductionunclassified